IMPLEMENTASI PEMBENTUKAN KARAKTER MELALUI PROGRAM BOARDING SCHOOL SMP ARDANIAH KOTA SERANG - Siti Magesaharani; Busthomi Ibrohim (Tarbawi, 2019)
The purpose of this research is to analyse the formation of character in students of Junior High School Ardaniah Boarding School Serang Banten. Research methods using qualitative descriptive method. Data collection techniques using observation, interviews, and documentation. Triangulation was done by way of rechecking the information interview results with the results of observation and documentation. The research found that the formation of character in the Boarding School Program Junior Ardaniah is done through: 1) academic activities, either intrasekolah or ekstrasekolah; 2) religious activities, such as: Islamic studies, the study of the book of yellow, muhadhoroh, memorizing the Qur'an, Qur'an tahfidz and Lughotul al-Ta'lim al Arabia; 3) activity skills, such as: activities The cultivation of Plants through tissue culture of language skills, and information and Communication Technology skills. The characters are observed is 1) religious, attitudes, and behavior; 2) disciplines3) honest. 4) independent, 5) responsibility towards themselves, society, environment, country and God Almighty. Keywords: Boarding school, character education, religious discipline